THE pH EFFECT AGAINST HYDROLYSIS OF FISH PROTEIN FROM MUDSKIPPER (Periophthalmus minitus) USING ALCALASE ENZYME - Indah Khairunnisa; Edison Edison; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study was aimed to determine the effect of pH against hydrolysis of fish protein from mudskipper (Periophthalmus minitus) using alcalase enzyme and to determine the best pH of mudskipper protein hydrolysis. The used method was an experimental method with A non-factorial Completely Randomized Design (CRD) consisting of 3 levels of treatment namely P1(pH 6.5), P2(pH 7.5) and P3 (pH 8.5). The observed parameters were the analysis of protein and moisture on mudskipper flour, the yield of mudskipper flour,the analysis of non-protein nitrogen and protein using lowry method on mudskipper protein hydrolysate. The results showed that the chemical analysis of mudskipper flour obtained 8.85% moisture, 86.56% protein, and the yield of 74.6%. The P1treatment (pH 6.5) obtained the non-protein nitrogen of 8.24% and 9.81% protein. The P2treatment (pH 7.5) obtained the non-protein nitrogen of 11.02% and 8.58% protein. Furthermore, the P3treatment (pH 8.5) obtained the non-protein nitrogen 10.43% and 9.91% protein. Kata kunci: Enzyme alcalase, hydrolysis of fish, mudskipper